Multiscale Transparent Electrode Architecture for Efficient Light Management and Carrier Collection in Solar Cells - Boccard, Mathieu; Battaglia, Corsin; Hänni, Simon; Söderström, Karin; Escarré, Jordi; Nicolay, Sylvain; Meillaud, Fanny; Despeisse, Matthieu; Ballif, Christophe (Nano letters, 2012)
The challenge for all photovoltaic technologies is to maximize light absorption, to convert photons with minimal losses into electric charges, and to efficiently extract them to the electrical circuit. For thin-film solar cells, all these tasks rely heavily on the transparent front electrode. Here we present a multiscale electrode architecture that allows us to achieve efficiencies as high as 14.1% with a thin-film silicon tandem solar cell employing only 3 μm of silicon. Our approach combines the versatility of nanoimprint lithography, the unusually high carrier mobility of hydrogenated indium oxide (over 100 cm2/V/s), and the unequaled light-scattering properties of self-textured zinc oxide. A multiscale texture provides light trapping over a broad wavelength range while ensuring an optimum morphology for the growth of high-quality silicon layers. A conductive bilayer stack guarantees carrier extraction while minimizing parasitic absorption losses. The tunability accessible through such multiscale electrode architecture offers unprecedented possibilities to address the trade-off between cell optical and electrical performance.